Assessing Self-Confidence In Ict Accounting Education - Listiadi, Agung (International Journal of Educational Research & Social Sciences, 2023)
In Indonesia itself, the use of ICT, especially in education, is still lacking. Meanwhile, in facing the globalization era of the 21st century, the use of ICT is a necessity to increase the effectiveness and efficiency of performance, including in the teaching and education process. The purpose of this research is to find out the teacher's perception in education using ICT. To answer the formulation of the problem in this study, a descriptive research method was used. Descriptive research is a research method used to find the widest possible knowledge of the object of research at a certain time. This research method also aims to explain or describe a situation, event, object or person, or anything related to variables that can be explained. For the purpose of data analysis and hypothesis testing by Path Analysis and Sobel tests were used. The research sample used proportional random sampling technique, using path analysis (Path) and sobel test (mediation test). Based on the results and discussion of the study, it was concluded that attitudes interpreted in the context of cognition, affection and conation are able to mediate the relationship between perceived usefulness and self-confidence. The results of the mediation test produce a relationship pattern, namely the perception of usefulness with confidence can be explained either directly or through the mediation of attitudes towards the use of accounting computer applications. For wider interests not only in the field of education, future research can be directed at the use of public information system applications, by adding the dependent variable costs and benefits as well as the independent variable actual use.